Prerequisites, barriers and opportunities in care for Q-fever patients: a Delphi study among healthcare workers - Iris M. Brus; Inge Spronk; Juanita A. Haagsma; Vicki Erasmus; Annemieke de Groot; Alfons G. M. Olde Loohuis; Madelon B. Bronner; Suzanne Polinder (BMC Health Services Research, 2023)
Abstract Background Q-fever is a zoonotic disease that can lead to illness, disability and death. This study aimed to provide insight into the perspectives of healthcare workers (HCWs) on prerequisites, barriers and opportunities in care for Q-fever patients. Methods A two-round online Delphi study was conducted among 94 Dutch HCWs involved in care for Q-fever patients. The questionnaires contained questions on prerequisites for high quality, barriers and facilitators in care, knowledge of Q-fever, and optimization of care. For multiple choice, ranking and Likert scale questions, frequencies were reported, while for rating and numerical questions, the median and interquartile range (IQR) were reported. Results The panel rated the care for Q-fever patients at a median score of 6/10 (IQR = 2). Sufficient knowledge of Q-fever among HCWs (36%), financial compensation of care (30%) and recognition of the disease by HCWs (26%) were considered the most important prerequisites for high quality care. A lack of knowledge was identified as the most important barrier (76%) and continuing medical education as the primary method for improving HCWs’ knowledge (76%). HCWs rated their own knowledge at a median score of 8/10 (IQR = 1) and the general knowledge of other HCWs at a 5/10 (IQR = 2). According to HCWs, a median of eight healthcare providers (IQR = 4) should be involved in the care for Q-fever fatigue syndrome (QFS) and a median of seven (IQR = 5) in chronic Q-fever care. Conclusions Ten years after the Dutch Q-fever epidemic, HCWs indicate that the long-term care for Q-fever patients leaves much room for improvement. Facilitation of reported prerequisites for high quality care, improved knowledge among HCWs, clearly defined roles and responsibilities, and guidance on how to support patients could possibly improve quality of care. These prerequisites may also improve care for patients with persisting symptoms due to other infectious diseases, such as COVID-19.